MEMBANGUN CLOUD COMPUTING UNTUK MANAGEMEN DATA PADA UNIVERSITAS ISLAM LAMONGAN - Agus Junaidi; Retno Wardhani; Masruroh Masruroh (Universitas Islam Lamongan, 2018)
To improve the efficiency of work activity management at Islamic University of Lamongan requires a service system that can help the work of management, especially data management service / file then the wake of data management services with website technology built in network of private University, website service is in the cloud Computing Local Service was built from a virtual server with a Debian 8 operating system and a server residing within the Proxmox operating system. The stages of the development of this service system include the creation of cloud services is done through several stages, namely the stage of network design, the stage of installing the operating system Proxmox, the stage of creating a VE server in proxmox, the stage of installing the VE server with debian8, the stage of configuring the VE server to web server and domain Server, implementation and testing stages. And also the stages of making management services through several stages, namely the design phase of the context diagram, the phase make usecase service diagram, create an activity diagram, the stage of making sequence diagram, and interfaces design stage